202k views
2 votes
Solve the system of equationsx + y = 52x - y = -2

User Hfimy
by
6.1k points

1 Answer

4 votes

Lets number the equations;

x + y = 5 -----i

2x - y = -2​ -----ii

Let's solve this using the substitution method, lets rewrite equation i as;

x = 5 - y

Substitute this into the equation ii

2(5 - y) - y = -2

10 - 2y - y = -2

Collect like terms

10 + 2 = 3y

12 = 3y , y = 12/3 = 4

Lets substitute y = 4 in equation i, we would have

x + 4 = 5

x = 5-4 = 1

Therefore,

x = 1

y = 4

User Lalli
by
6.3k points